Дочь некроманта. Вернуть посох: летписи Разлома / Ник Перумов, Ник - Перумов Ник (Эксмо, 2006)
Экземпляры: аб. ЦБ (2017.18.09) / Инвентарный номер: 3298 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: П27 / ББК: 84 (2 Рос=Рус)6